A Comparative Study of Control Methods for Induction Motor and High Performance Z-source Inverter - Pham Cong Thanh; Shen An Wen (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Design studies of the most suitable controller for the speed of induction motor (SIM) and peak DC-link voltage (PDV) of high performance z-source inverter (HP-ZSI) greatly affects performance of hybrid electric vehicles. This paper is to give comprehensive analyses comparison and evaluations of the different control techniques as PI controller, self-tuning fuzzy PI controller (SFP) and genetic algorithms optimal tuning gains of the PI controller for controlling the SIM based on criteria of the integral of the absolute value of speed error. With control PDV, this paper also presents comparisons of the different techniques as PI controller, fuzzy logic controller, SFP based on observation of its response and total harmonic distortion of current. All methods are applied to the closed loop of the SIM which relies on direct torque control combined with modified space vector modulation and closed loop of PDV in HP-ZSI. These methods are verified by Matlab software. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2445